I demand an Explanation! ... The Importance of the Motivation of the Administrative Act - León Luna, Luis Miguel (2015)
In this article, the author stresses the importance of the right to proper motivation in the context of administrative procedures. In that sense, he states that all public bodies are required to issue administrative acts duly substantiated, because this is a requirement which, if unobserved, generates the nullity of the act. But beyond to validate administrative act, the author argues that the main benefit of meeting the proper motivation lies in the improvement of the interaction between the taxpayers and the Public Administration, generating greater confidence in state activity and promoting the development of economic activities with increasing levels of formality.